Does Renewable Energy Sector Affect Industrialization-CO2 Emissions Nexus in Europe and Central Asia? - Grzegorz Mentel; Waldemar Tarczyński; Marek Dylewski; Raufhon Salahodjaev (Energies, 2022)
Current research assesses the impact of industrialization and the renewable energy sector on greenhouse gas emissions, proxied by CO2 emissions in Europe and Central Asia. We rely on a two-step system GMM estimator on a sample of 48 countries over the period 2000–2018. Empirical results show that industrialization has a positive effect on CO2 emissions: a 10% increase in industry value added as % of GDP leads to an increase of 2.6% in CO2 emissions. In contrast, renewable energy mitigates CO2 emissions. Ten percentage points increase in renewable energy consumption reduces CO2 emissions per capita by 2.2%. The interaction term between renewable energy and industry value added is negative, suggesting that renewable energy consumption compensates for the negative effect of industrialization on environmental quality. Our main results also confirm the U-shaped inverted relationship between GDP per capita and CO2 emissions. Our study has a number of policy implications and avenues for future research.